Kepentingan Indonesia Terhadap One Belt One Road (OBOR) Dalam Upaya Mewujudkan Poros Maritim Dunia - Kris Naning Soviyaningsih (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2019)
This research figures out the national interest of Indonesian State regarding to One Belt One Road policy initiated by Tiongkok in realizing Indonesian as Global Maritime Fulcurm. The research discusses the problem of foreign policy of Indonesian while as a part of the OBOR initiative to fulfill national interest as a country that has become Global Maritime Fulcurm. The research utilizes in descriptive qualitative research metode along with documentation studies and use concept of foreign policy from the country to seeing the cooperation between Indonesia and Tiongkok. Through this cooperation, OBOR has a role in realizing Indonesian’s foreign policy as Global Maritime Fulcurm.